Microbiome–volatile metabolome analysis reveals aroma regulation driven by microbial niche competition in Jinggang honey pomelo wine - Wu, Yang; Li, Weiwei; Shi, Jianan; Zhang, Zhihao; Jing, Cheng; Sheng, Jianqi; Li, Zexia; Shi, Xiaowen; Liu, Dingkun; He, Li; Sun, Huimin (Frontiers in Microbiology, 2026)
IntroductionMicrobial succession in fruit wine has been reported, but the ecological mechanisms linking niche competition to aroma formation remain poorly understood. To test the hypothesis that niche competition between microbial communities significantly influences aroma formation in pomelo wine, the flesh of Jinggang honey pomelo was subjected to semi-inoculation fermentation to produce Jinggang honey pomelo wine.MethodsHigh-throughput amplicon sequencing technology was used to investigate the evolving microbial community during the fermentation process of pomelo wine. The changes in volatile compounds were measured using headspace solid phase microextraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC-MS).ResultsThe dominant taxa in the wine were Weissella, Pediococcus, Lactiplantibacillus, Saccharomyces, Komagataella, Wickerhamomyces, and Aspergillus. The microbiota shifts were associated with dynamic changes in physicochemical properties, and they altered the pH, alcohol content, total soluble solids, and overall acidity. Principal component analysis (PCA), orthogonal partial least squares-discriminant analysis (OPLS-DA), and relative odor activity value analysis identified 17 key volatiles. A correlation network analysis revealed that Lactiplantibacillus and Aspergillus were strongly associated with various flavor molecules.DisscussionThe present findings suggested that inter-kingdom niche competition between fungi and bacteria plays a pivotal role in shaping the aroma profile of pomelo wine, offering new insights for targeted aroma regulation.